Chronic Blood Pressure Reductions and Increments in Plasma Nitric Oxide Bioavailability - Tomeleri, Crisieli M.; Marcori, Alexandre J.; Ribeiro, Alex Silva; Gerage, Aline Mendes; Padilha, Camila de Souza; Schiavoni, Durcelina; Souza, Mariana F.; Mayhew, Jerry L.; do Nascimento, Matheus Amarante; Venturini, Danielle; Barbosa, Decio Sabbatini; Cyrino, Edilson Serpeloni (International Journal of Sports Medicine, 2017)
This study analyzed the effects of 12 weeks of resistance training (RT) on resting blood pressure (BP) and plasma levels of nitric oxide metabolites (NOx) in pre- and hypertensive older women, and evaluated the relationship between these 2 parameters. Thirty-five older women (68.2±5.7 years, 70.0±14.4 kg, 157.1±6.4 cm, 28.3±5.0 kg.m−2) were randomly allocated into a training group (TG; n=17), which performed a 12-week RT program, and a control group (CG; n=18), which did not perform any physical exercise. Anthropometry, one repetition maximum (1RM), body composition analysis by dual energy X-ray absorptiometry, blood samples, and resting BP were measured. There was a significant interaction for all variables analyzed, in which reductions of systolic BP (−8.5%), diastolic BP (−8.4%), and mean arterial pressure (−8.5%), and increases of NOx (+35.2%) were observed only for the TG. Moreover, a negative and significant correlation was observed (P<0.05; r=−0.63) between NOx and systolic BP in the TG. Results suggest that a 12-week RT program is sufficient to induce reductions in BP in pre- and hypertensive older women and that the decrease in systolic BP is associated with an increase in plasma NOx concentration.
Keywords: aging; strength training; hypertension; systolic blood pressure; older women; resistance training